Changrun Formula Relieves Functional Constipation by Improving Intestinal Motility in Rats - Qiuping Xiao; Yanqiu Hong; Xuesi Geng (Gastroenterology Research and Practice)
Conclusions: CRF likely improves intestinal motility by targeting HCN1 and HCN2 ion channels and the SCF/c-kit signaling pathway, thereby alleviating FC symptoms in rats.